A novel anemia associated with membranous cytoplasm degeneration in 16 patients: an ultrastructural study. (4th July 2018) - Ru, Yong-Xin; Dong, Shu-Xu; Li, Yuan; Zhao, Shi-Xuan; Liang, Hao-yue; Zhu, Xiao-fan; Zheng, Yi-zhou; Zhang, Feng-kui
ABSTRACT: Sixteen patients with mild anemia and hemolysis were difficult to be classified into any known category based on laboratory examinations and light microscopy. To make a definite diagnosis and investigate the pathomechanism, ultrastructural study was performed on erythroid cells from 16 patients. Transmission electron microscopy demonstrated a series of alterations of cytoplasm, including cytoplasm sequestration, membranous transformation, and degeneration in erythroblasts and reticulocytes at different stages. The affected erythroblasts were usually complicated with chromatin condensation, karyorrhexis, nuclear membrane lysis, and megaloblastic changes. The reticulocytes with the cytoplasm alterations had a huge size from 10 um to 15 um in diameter. The membranous cytoplasm degeneration revealed a unique pathomechanism of dyserythropoiesis and ineffective erythropoiesis in 16 patients with anemia, and suggested a novel anemia category though more details remained to be investigated.